THE CONTINUUM EMISSION OF THE ORION NEBULA - MENDEZ, ME (UNAM, Observatorio Astronómico Nacional, CD MEXICO, DF, MEX, 1965)
The continuum produced by the brightest region of the Orion Nebula has been observed photoelectrically. The spectral range covered is from ?~3500 to ?~11000. The various processes contributing to the continuum energy have been studied. The component provi
BOL OBS TONAN TACUB
Keywords: CONTINUUM EMISSION, ORION NEBULA; ASTRONOMIA Y ASTROFISICA; COSMOLOGIA Y COSMOGONIA; ESTRELLAS